Everybody wants to rule the world : a novel [large type] - Atkins, Ace (William Morrow Large Print, an imprint of HarperCollins Publishers, 2025)
"It's 1985, what will soon become known as "The Year of the Spy," and fourteen-year-old Peter Bennett is convinced his mom's new boyfriend is a Russian agent. "Gary" isn't in the phone book, has an unidentifiable European accent, and keeps a gun in the glove box of his convertible Porsche. Peter thinks Gary only wants to get close to his mom because she works at Scientific Atlanta, a lab with big government contracts. But who is going to believe him? He's just a kid into BMX and MTV. But after another woman who works at the lab is killed, Peter recruits an unlikely pair of allies-a has-been pulp writer and muckraker named Dennis Hotchner and his drag performer buddy and heavy, Jackie Demure. Both soon become the target of an unhinged Russian hitman (Is it Gary? Maybe!) with a serious Phil Collins obsession. Meanwhile, Sylvia Weaver, a young, Black FBI agent, investigates Scientific Atlanta in the wake of the employee's murder and discovers a nest of Russian spies in the Southern "city too busy to hate." Little does she know her investigation is being thwarted by a seriously compromised colleague in Washington, D.C., who is in league with a lovesick, hypochondriac KGB defector who is playing both sides of the Cold War to his benefit. As Ronald Reagan and Soviet Premier Mikhail Gorbachev prepare for a historic nuclear summit in Geneva, what happens in Atlanta might change the course of the Cold War, the twentieth century, and Peter Bennett's freshman year of high school"--